Terapi Kelompok Terapeutik Anak dengan Orang Tua dan Guru Meningkatkan Perkembangan Mental Anak Usia Sekolah - Dian Istiana; Budi Anna Keliat; Tuti Nuraini (Jurnal Ners, 2011)
Introduction: School aged called as intelectual time in industrial development stage. Industrial development stage is important in human development stages. The purpose of this tudy was to know the effect of school aged therapeutic group therapy to mental development.Methods: The design was quasi experimental pre-post test with control group. One hundred and sixteen children at 9–11 years old were used as sample of this study that divided to 38 children on first intervention group (childparents), 36 children on second intervention group (child-teacher) and 40 children on control group.Results: Result of the study showed that cognitive, psychomotor and industrial development ability had increased significantly after therapeutic group therapy was given (p-value < 0.005) in intervention group.Conclusion: The study was recomended in child-parents and child-teacher to increase mental development in school aged children.